2016
DOI: 10.1128/genomea.00644-16
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequence of the Psychrophilic Bacterium Tenacibaculum ovolyticum Strain da5A-8 Isolated from Deep Seawater

Abstract: Some bacterial species of the genus Tenacibaculum, including Tenacibaculum ovolyticum, have been known as fish pathogens in the sea. So far, the only published genome sequence for this genus is for Tenacibaculum dicentrarchi, which could also be a fish pathogen. Strain da5A-8, showing 100% identity to the 16S rRNA gene sequence of T. ovolyticum DSM 18103T, was isolated from seawater at a depth of 344 m in Kochi, Japan, and grew optimally at 10 to 20°C. The genome sequence of strain da5A-8 revealed the possible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 9 publications
0
20
0
Order By: Relevance
“…A BLAST search of the Tenacibaculum OTU sequence revealed the highest level of similarity (100% identity) with the 16s rRNA gene sequence of Tenacibaculum ovolyticum strain da5A-8, a deep-sea fish pathogen with virulence factors similar to other Tenacibaculum sp . [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…A BLAST search of the Tenacibaculum OTU sequence revealed the highest level of similarity (100% identity) with the 16s rRNA gene sequence of Tenacibaculum ovolyticum strain da5A-8, a deep-sea fish pathogen with virulence factors similar to other Tenacibaculum sp . [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, T. maritimum does not possess a proteorhodopsin-encoding gene as identified in close relatives such as Polaribacter , Dokdonia , or Psychroflexus species, suggesting the inability of this bacterium to use light to generate proton motive force. Comparison with the available genomes of the three other fish-pathogenic Tenacibaculum species Tenacibaculum dicentrarchi , Tenacibaculum ovolyticum , and T. soleae ( Grothusen et al, 2016 ; Lujan et al, 2016 ; Teramoto et al, 2016 ), has revealed striking differences in virulence strategies as most, if not all, the aforementioned predicted toxins ( Table 1 ) are absent from the genomes of the latter species. These elements point to very different paths in the evolution of virulence as suggested using a subset of core-genome genes ( Habib et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Tenacibaculum sp. have also been recovered from marine waters [ 21 , 22 , 23 ] and biofilms [ 24 , 25 ]. The presence of Tenacibaculum sp.…”
Section: Introductionmentioning
confidence: 99%